Emricasan Ameliorates Portal Hypertension and Liver Fibrosis in Cirrhotic Rats Through a Hepatocyte‐Mediated Paracrine Mechanism. Issue 7 (22nd April 2019) - Gracia‐Sancho, Jordi; Manicardi, Nicolò; Ortega‐Ribera, Martí; Maeso‐Díaz, Raquel; Guixé‐Muntet, Sergi; Fernández‐Iglesias, Anabel; Hide, Diana; García‐Calderó, Héctor; Boyer‐Díaz, Zoe; Contreras, Patricia C.; Spada, Alfred; Bosch, Jaime
Abstract : In cirrhosis, liver microvascular dysfunction is a key factor increasing hepatic vascular resistance to portal blood flow, which leads to portal hypertension. De‐regulated inflammatory and pro‐apoptotic processes due to chronic injury play important roles in the dysfunction of liver sinusoidal cells. The present study aimed at characterizing the effects of the pan‐caspase inhibitor emricasan on systemic and hepatic hemodynamics, hepatic cells phenotype, and underlying mechanisms in preclinical models of advanced chronic liver disease. We investigated the effects of 7‐day emricasan on hepatic and systemic hemodynamics, liver function, hepatic microcirculatory function, inflammation, fibrosis, hepatic cells phenotype, and paracrine interactions in rats with advanced cirrhosis due to chronic CCl4 administration. The hepato‐protective effects of emricasan were additionally investigated in cells isolated from human cirrhotic livers. Cirrhotic rats receiving emricasan showed significantly lower portal pressure than vehicle‐treated animals with no changes in portal blood flow, indicating improved vascular resistance. Hemodynamic improvement was associated with significantly better liver function, reduced hepatic inflammation, improved phenotype of hepatocytes, liver sinusoidal endothelial cells, hepatic stellate cells and macrophages, and reduced fibrosis. In vitro experiments demonstrated that emricasan exerted its benefits directly improving hepatocytes' expression of specific markers and synthetic capacity, and ameliorated nonparenchymal cells through a paracrine mechanism mediated by small extracellular vesicles released by hepatocytes. Conclusion : This study demonstrates that emricasan improves liver sinusoidal microvascular dysfunction in cirrhosis, which leads to marked amelioration in fibrosis, portal hypertension and liver function, and therefore encourages its clinical evaluation in the treatment of advanced chronic liver disease. Abstract : One‐week emricasan promoted a significant amelioration in portal hypertension and hepatic microcirculation in experimental cirrhosis. Underlying mechanisms included direct improvement in hepatocytes phenotype, which paracrinally leads to fibrosis improvement, better endothelial function, and less inflammation.